Sustainable happiness : live simply, live well, make a difference - Van Gelder, Sarah (BK, Berrett-Koehler Publishers, Inc., San Francisco, a BK Life Book, 2014)
Sarah van Gelder and her colleagues at YES! Magazine have been exploring the meaning of real happiness for eighteen years. In this volume, they marshal research, in-depth essays, and personal stories that lead to a life-altering conclusion: what makes us truly happy are the depth of our relationships, the quality of our communities, our opportunities to make a contribution, and the renewal we receive from the natural world.